If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(a + 12) = 20 Reorder the terms: 2(12 + a) = 20 (12 * 2 + a * 2) = 20 (24 + 2a) = 20 Solving 24 + 2a = 20 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 2a = 20 + -24 Combine like terms: 24 + -24 = 0 0 + 2a = 20 + -24 2a = 20 + -24 Combine like terms: 20 + -24 = -4 2a = -4 Divide each side by '2'. a = -2 Simplifying a = -2
| 6x-1+3x-8=90 | | f=a+b+c/3 | | 2a+12=32 | | 78y-44y= | | lx-1l=3 | | 54.313*12.09= | | 1+44y-44y= | | 3a+2c-5= | | 4(x+1/4)=16 | | 5b+2a+4= | | -2k+28=21k+49 | | n=70 | | -9x-6=x-30 | | y=x+y/2 | | 7x+7=18x-4 | | 0=(.2-x)*(.0002-3x)*(.0002-3x)*(.0002-3x) | | x=3+0.25y | | x=3+0.25y | | 3(15)+5=5(15)-25 | | -1/3=5 | | e/6=12/4 | | 12/4=d/8 | | (z+8)(z-11)= | | -9(x-9)=(x+63) | | t=14 | | -3(1)=3 | | 10y+20x=130 | | 9x^2-18xy+8y=0 | | x+3/5=2 | | c+3/5=2 | | 18+a=16 | | 2*3x+11=6x+4 |